Implementasi Kebijakan Sistem Kalkukasi Simulasi Retribusi (Sikasir) Online Dalam Peningkatan Pelayanan Di Dpmptsp Kota Depok - Meyandasari, Berlian; Mulyadi, Mohammad (Institut Ilmu Sosial dan Manajemen STIAMI, 2024)
Retributions became a complex problem in 2023 after the Depok City Inspectorate carried out an inspection at the Depok City DPMPTSP and found that there were retribution receivables amounting to IDR 16,000,000,000.00 caused by many building permit applicants who did not continue with their building permits because they did not pay the retribution. Applicants for building permits do not pay their levy bills due to several factors, one of which is that the applicant does not know the amount of the levy before carrying out the permit so that when the levy bill appears and the amount is high, the applicant feels that someone is